The Feminization of Deteriorated Labor Force Participation In Egypt: 1990 – 2024 - Gamal Nour El Din, Mennan (AUC Knowledge Fountain, 2025)
The purpose of this thesis is to explain why female labor force participation deteriorated in quantity and in quality despite the recent rise in female educational attainment levels over the past three decades (1990 – 2024). On the one hand, labor participation declined, whereas on the other hand, female informal employment remains high in Egypt. This thesis dissertation utilizes a qualitative research methodology through both secondary data in the form of descriptive statistics on the phenomenon of female labor force participation as well as primary data in the form of six in-depth expert interviews with experts in the fields of gender, political economy, labor economics, public and social policy, development, and impact-assessment. The review of the literature addresses the main factors affecting the phenomenon of female labor force participation and the high presence of women in informal employment, identifying education as one of the most significantly positive factors affecting FLFP. This thesis contributes to the literature by expanding on the literature pertaining to the role played by labor regulating institutions and their policies on female formal labor force participation and subsequently female informal employment, through a gendered lens. This thesis argues that this phenomenon of low female labor force participation and high female presence in informality can be linked to Egypt’s educational institutional gender neutrality & non-gender inclusive higher and technical & vocational educational (TVET) policies, resulting in the prevalence of the “education-occupation mismatch” as well as the gendered ICT skills disparity — especially regarding gender integration, leading to a failure in the translation of increased female education into meaningful integration in the job market. In an effort to contribute to enhancing the Egyptian labor market for females, this thesis dissertation sheds light on the significance of setting forth gender-preferential regulatory frameworks and policies by labor-regulating state institutions – allowing for the translation of high female educational attainment levels to higher female formal labor force participation rates and lower female informal employment in vulnerable and precarious conditions.